Spatial transcriptomes and microbiota reveal immune mechanism that respond to pathogen infection in the posterior intestine of Sebastes schlegelii - Min Cao; Ting Xue; Huijun Huo; Xiaoyan Zhang; Ning Ning Wang; Xu Yan; Chao Li (Open Biology, 2023)
The intestine is a site of immune cell priming at birth. Therefore, spatial transcriptomes were performed to define how the transcriptomic landscape was spatially organized in the posterior intestine of Sebastes schlegelii following Edwardsiella piscicida infection. In the healthy condition, we identified a previously unappreciated molecular regionalization of the posterior intestine. Following bacterial infection, most immune-related genes were identified in mucosa layer. Moreover, investigation of immune-related genes and genes in immune-related KEGG pathways based on spatial transcriptomes shed light on which sections of these genes are in the posterior intestine. Meanwhile, the high expression of genes related to regeneration also indicated that the posterior intestine was responding to the invasion of pathogens by constantly proliferating new cells. In addition, the increasing microbiota communities indicated that these bacteria maintained posterior intestine integrity and shaped the mucosal immune system. Taken together, spatial transcriptomes and microbiota compositions have significant implications for understanding the immune mechanism that responds to E. piscicida infection in the posterior intestine of S. schlegelii, which also provides a theoretical basis for the spatial distribution of immune genes and changes in bacterial flora in other teleosts in the process of resisting pathogens.